Estimativa da não adesão ao tratamento da malária em área endêmica no Marajó estado do Pará - ALMEIDA, Eduardo Dias (Universidade Federal do Pará, 2017)
The association of Chloroquine (CQ) and Primaquine (PQ) is used as first-line treatment for malaria caused by Plasmodium vivax in Brazil. Treatment failure of this association is recognized worldwide and frequently reported. Multifactorial, involving related to the host, the vector and the etiological agent variables. Among these, treatment adherence is critical to establish the efficacy and effectiveness of antimalarial drugs, because the behavior of non-compliance tends to increase the rates of parasite recurrence and foster the emergence of strains resistant to antimalarial drugs. Despite the high incidence of P. vivax malaria in the Brazilian Amazon basin, few studies have evaluated treatment adherence and behavioral factors and environmental determinants. This study aimed to estimate the rate of non-adherence to treatment of P. vivax malaria in the municipality of Anajás, PA. We conducted a survey of demographic data (age, location, gender) and observational studies on the perception of the local population about the disease and its treatment. Then become a validated instrument to measure non-adherence to treatment in different metrics, based on the study by Morisky et al. (1986), with the addition of an item on the self-replication of doses for use in patients with P. vivax malaria. Finally, we proposed an evaluation model of non-adherence based on therapeutic drug monitoring of pharmacokinetic parameters of CQ, considering different scenarios of noncompliance. The results showed that the disease occurs in both sexes and in most cases are from rural areas. Risk factors such as gender, origin, parasitaemia at admission to treatment and age had no significant impact on rates of nonadherence. However, the abandonment of treatment to feel better, the need to return to work, or worse activities, the adverse effects of CQ, were the key behaviors for non-compliance to full treatment regimen. The instrument for measuring non-adherence, consisting of five items presented satisfactory validation parameters, in particular in its Likert scale dichotomized so that estimated non-adherence to the therapeutic regimen in 33.3%. After construction and validation of the mono-compartmental pharmacokinetic model by non-linear regression and evaluation of various scenarios for non-adherence, it is found that the loss of two consecutive doses without replacement was regarded as the only scenario that can significantly change the pharmacokinetic parameters and CK interfere with the therapeutic response.